Policing the port, watching the city. Manifestations of organised crime in the port of Genoa - Sergi, Anna (Policing and society, 2021)
This article will present the results of a qualitative research into organised crime in the port of Genoa, Italy’s largest port, by looking at the challenges of policing the port space. Through the case of Genoa, the paper reflects on how organised crime manifests across three trajectories in seaports: trafficking through the port, infiltration in the port economy and governance of the port management. This paper argues that the space and geography of the port-city relationship are key to understand how and to what extent different organised criminal groups act in and around the port and within global drives. An integrated approach between urban criminology and organised crime studies is needed to better map the very complex picture of organised criminality in the port within the city.